Mainstreaming agricultural biological diversity across sectors through NBSAPs: Missing Links to Climate Change Adaptation, Dietary Diversity and the Plant Treaty - Lapena, Isabel; Halewood, Michael; Hunter, Danny (2016)
This Information Note presents a summary of an analysis of the revised NBSAPs that were submitted by 119 countries to the CBD Secretariat prior to 20 November 2016. The study focused on how agrobiodiversity has been mainstreamed across sectors through the NBSAPs